2022
DOI: 10.31234/osf.io/xwu4j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroimaging in psychedelic drug development: Past, present, and future

Abstract: Psychedelic therapy (PT) is an emerging paradigm with great transdiagnostic potential for treating a range of psychiatric disorders, including depression, addiction, eating disorders, post-traumatic stress disorder, and others. ‘Classic’ serotonergic psychedelics, such as psilocybin, lysergic acid diethylamide (LSD), N, N-Dimethyltryptamine (DMT) and 5-methoxy-N,N-dimethyltryptamine (5-MeO-DMT), form the main focus of this movement, but other substances including ketamine, 3,4-Methylenedioxymethamphetamine (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…In this context, more work is needed to understand how the increased neural plasticity induced by psychedelics (see Calder and Hasler, 2023) is linked to the changes in brain circuitry and increase in "entropy" of neural networks (Carhart- Harris and Friston, 2019;Inserra et al, 2021a;Herzog et al, 2023;Ort et al, 2023;Wall et al, 2023). The "acute" and "rebound" activity could be in opposite directions when considering brain metabolism (see Vollenweider et al, 1997;Carhart-Harris et al, 2012).…”
Section: Psychedelic Drugs: Possible Brain Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, more work is needed to understand how the increased neural plasticity induced by psychedelics (see Calder and Hasler, 2023) is linked to the changes in brain circuitry and increase in "entropy" of neural networks (Carhart- Harris and Friston, 2019;Inserra et al, 2021a;Herzog et al, 2023;Ort et al, 2023;Wall et al, 2023). The "acute" and "rebound" activity could be in opposite directions when considering brain metabolism (see Vollenweider et al, 1997;Carhart-Harris et al, 2012).…”
Section: Psychedelic Drugs: Possible Brain Mechanismsmentioning
confidence: 99%
“…Moreover, psychedelics seem to "disrupt" connectivity, especially in resting-state networks such as the DMN, also resulting in induced modifications of the functional connectivity between these circuits and other brain networks (Carhart-Harris et al, 2013, 2017Daws et al, 2022;Felsch and Kuypers, 2022) that, for example, may favor "goaldirected" behaviors. In this context, a series of different models have been proposed that attempt to explain the various effects of doses of psychedelic drugs on the brain, also making assumptions about their induced neural modulations (e.g., DMN; Carhart- Harris and Friston, 2019;Vollenweider and Preller, 2020;Daws et al, 2022;Doss et al, 2022;Gattuso et al, 2023;Herzog et al, 2023;Wall et al, 2023). Nonetheless, it is still not clear what is the main brain target of the therapeutic potential of, for example, psilocybin 10.3389/fnhum.2024.1402549 (Gattuso et al, 2023).…”
Section: Psychedelic Drugs: Possible Brain Mechanismsmentioning
confidence: 99%
“…A placebo-controlled study of psychedelic-naive healthy individuals given ayahuasca revealed increased ACC connectivity within the SN, decreased PCC connectivity within the DMN and increased connectivity between the SN and DMN 1 day after ayahuasca ( 131 ). Intriguingly, increased global coupling and functional connectivity between SN and DMN nodes have been found under acute psilocybin administration ( 141 ) but future work, ideally combining multimodal molecular and functional neuroimaging ( 142 ), is needed to elucidate how mid- and long-term functional interactions of both networks are changed by psychedelic therapy in populations with addiction and how these relate to prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these methods have provided varying levels of detail on the nuances of molecular dysfunction in addiction and hence could be used as a proxy to explore how such parameters may predict response to psychedelic therapies and if psychedelic therapies restore any of the observed molecular deficits. More recently, human molecular neuroimaging has offered insight into the neurochemical mechanism(s) of action of psychedelics although to a much less extent than fMRI ( 142 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation